PERANAN MAHASISWA DALAM BELA NEGARA MENGGUNAKAN MEDIA SOSIAL DENGAN KONTEN KEKINIAN - Sri Hartinah; Said Bambang Nurcahya (Jurnal Sosio dan Humaniora (SOMA), 2022)
Z Generation is the generation that was born in the range of 1996 to 2012. Gen Z is the generation that was born after the era of the millennial generation, Gen Z is the transition from the millennial generation with increasingly developing technologies, Gen Z is also called iGeneration, the internet generation or generation net. People who belong to the Z gene era have something in common with the millennial generation. However, Gen Z is considered capable of implementing all activities at one time, such as playing social media on cellphones, browsing with PCs, and listening to music. Gen Z is considered capable of multi-tasking and doing all three of these activities at the same time. In addition, Gen Z is considered to have a close relationship with cyberspace and almost all activities are carried out in cyberspace, for countries this generation must be given understanding and direction in the integrity of the nation because there are many views of Radicalism and ideology that will divide the Unitary State of the Republic of Indonesia, so this research will review The role of Pajajaran Polytechnic Students ICB Bandung in maintaining the integrity of the Unitary State of the Republic of Indonesia by using social media and broadcasting with contemporary youth content and language so that it is easy for teenagers to digest and understand. College students and high school and vocational students in the city of Bandung. The research methodology of this journal uses descriptive analysis to describe it systematically and logically so that it can be used as a guide in determining the analysis and conclusions of a problem, so that the understanding of radicalism that divides the nation can be understood and understood as a whole. easy to digest, so one way is to use podcasts, social media, and information systems that are mixed in light and easy-to-digest language.